Seeded Growth Synthesis of Gold Nanotriangles: Size Control, SAXS Analysis, and SERS Performance - Kuttner, Christian; Mayer, Martin; Dulle, Martin; Moscoso, Ana; Lopez-Romero, Juan Manuel; Foerster, Stephan; Fery, Andreas; Perez-Juste, Jorge; Contreras-Caceres, Rafael (ACS Applied Materials and Interfaces, 2018)
We studied the controlled growth of triangular prismatic Au nanoparticles with different beveled sides for surface-enhanced Raman spectroscopy (SERS) applications. First, in a seedless synthesis using 3-butenoic acid (3BA) and benzyldimethylammonium chloride (BDAC), gold nanotriangles (AuNTs) were synthesized in a mixture with gold nanooctahedra (AuNOCs) and separated by depletion-induced flocculation. Here, the influence of temperature, pH, and reducing agent on the reaction kinetics was initially investigated by UV-vis and correlated to the size and yield of AuNT seeds. In a second step, the AuNT size was increased by seed-mediated overgrowth with Au. We show for the first time that preformed 3BA-synthesized AuNT seeds can be overgrown up to a final edge length of 175 nm and a thickness of 80 nm while maintaining their triangular shape and tip sharpness. The NT morphology, including edge length, thickness, and tip rounding, was precisely characterized in dispersion by small-angle X-ray scattering and in dry state by transmission electron microscopy and field-emission scanning electron microscopy. For sensor purposes, we studied the size-dependent SERS performance of AuNTs yielding analytical enhancement factors between 0.9 × 104 and 5.6 × 104 and nanomolar limit of detection (10-8-10-9 M) for 4-mercaptobenzoic acid and BDAC. These results confirm that the 3BA approach allows the fabrication of AuNTs in a whole range of sizes maintaining the NT morphology. This enables tailoring of localized surface plasmon resonances between 590 and 740 nm, even in the near-infrared window of a biological tissue, for use as colloidal SERS sensing agents or for optoelectronic applications.
CRIS-Team Scopus Importer:2022-04-14
Keywords: colloidal particles; gold nanotriangles; plasmonic platforms; seed-mediated approach; small-angle X-ray scattering; surface-enhanced Raman scattering; ultrasensitive detection